Exploring the Catalytic Efficiency of Copper-Doped Magnetic Carbon Aerogel for the Coupling Reaction of Isatin Oxime with Phenylboronic Acid Derivatives - Mudgal, Deeksha; Singh, Ravi Pratap; Yadav, Nisha; Bharti, Tapeesh; Mishra, Vivek (SynOpen, 2023)
A highly efficient catalyst, Cu-doped poly(N-[3-(dimethylamino)propyl]methacrylamide, acrylic acid, N-vinyl imidazole) (PDAI) magnetic carbon aerogel (CPIMCA), was successfully employed for the synthesis of isatin nitrone derivatives. The 3D porous CPIMCA catalyst demonstrated outstanding performance through the application of a coupling reaction between isatin oxime and phenylboronic acid derivatives, providing up to 98% yield of the required nitrone derivatives. Remarkably, the incorporation of copper within the polymeric structure of the magnetic carbon aerogel exhibited a significant influence on catalytic activity, even at a low overall copper content of approximately 2%. This was confirmed through EDX elemental mapping analysis, further establishing the competence of the catalyst for catalytic reactions. Comparative studies revealed that CPIMCA outperformed Cu(Oac)2 catalyst, providing a notable 10–15% increase in product yield. This superior performance can be attributed to the unique synergistic effect of copper, iron, and carbon aerogel as the polymeric matrix, highlighting the exceptional capabilities of CPIMCA as a catalyst.
Keywords: catalytic coupling reaction; recyclable magnetic catalyst; carbon aerogel; iron; copper doping